2003
DOI: 10.1046/j.1365-2249.2003.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans’ cells in the murine oral mucosa in the inductive phase of delayed type hypersensitivity with 1-chloro-2, 4-dinitrobenzene

Abstract: SUMMARYWe created a murine model of delayed-type hypersensitivity (DTH) to 1-chloro-2, 4-dinitrobenzene (DNCB). Using this murine model, we compared oral mucosal sensitization and skin sensitization for the difference in reaction during the elicitation phase. Evaluation of sensitizability, using the mouse ear swelling test (MEST) after oral mucosal or skin sensitization, showed that the ear swelling response peaked 24 h after challenge. The optimal induction concentration was 1·0% in both oral mucosal and skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In our study, all animals were sensitized either by percutaneous or submucosal administration. These results clearly indicate that NiSO 4 can sensitize via the oral mucosa similarly to other antigens such as DNCB 13) , although submucosal injection of an antigen does not completely simulate contact with dental materials as seen in a clinical setting. Furthermore, ear swelling was significantly greater in the skin-than in the oral mucosa-sensitized mice at 48 hr after challenge with NiSO 4 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, all animals were sensitized either by percutaneous or submucosal administration. These results clearly indicate that NiSO 4 can sensitize via the oral mucosa similarly to other antigens such as DNCB 13) , although submucosal injection of an antigen does not completely simulate contact with dental materials as seen in a clinical setting. Furthermore, ear swelling was significantly greater in the skin-than in the oral mucosa-sensitized mice at 48 hr after challenge with NiSO 4 .…”
Section: Discussionmentioning
confidence: 71%
“…In order to test this hypothesis, we need to compare skin and oral mucosa sensitization with nickel and oral tolerance for nickel in various models. Previous studies have shown that delayed-type hypersensitivity is induced in the oral mucosa by haptens such as 1-chloro-2, 4-dinitrobenzene (DNCB) 13) . However, a model for oral sensitization by metal ions such as those of nickel remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that mice were sensitized by application of the haptens DNCB or oxazolone to the oral mucosa, as well as the skin [1][2][3]16) . The present results are consistent with the results of these earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the sensitization experiments on BALB/c mice using a method which required no use of adjuvants 14,16) . The administration sites were the dorsal skin, bilateral buccal mucosa and esophageal/lower digestive tract mucosa.…”
Section: Mouse Ear Swelling Testmentioning
confidence: 99%
See 1 more Smart Citation